2000
DOI: 10.1093/humrep/15.8.1819
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcome of singleton pregnancies after IVF: a matched control study in four Dutch university hospitals

Abstract: In singleton pregnancies after IVF a high rate of preterm deliveries and an increased rate of small-for-gestational age (SGA) children in comparison to the general parturient population have been reported. However, due to differences between IVF mothers and their peers who conceived naturally, careful selection of the control group is necessary to assess whether IVF pregnancies really carry increased risks of adverse outcome. In our study 307 IVF pregnancies were compared with 307 control pregnancies after ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
100
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 34 publications
16
100
6
1
Order By: Relevance
“…In multiple pregnancies, however, there are differences with the highest rate observed in IVF (3.7 %). Previous publications report stillbirth rate in IVF population ranging between 1.7 and 3.9 % [20,38] which is in accordance with our stillbirths rate. A recent study in singleton pregnancies compared the risk of stillbirth between fertile women, sub fertile women and women pregnant after fertility treatment (IVF and non-IVF ART).…”
Section: Discussionsupporting
confidence: 93%
“…In multiple pregnancies, however, there are differences with the highest rate observed in IVF (3.7 %). Previous publications report stillbirth rate in IVF population ranging between 1.7 and 3.9 % [20,38] which is in accordance with our stillbirths rate. A recent study in singleton pregnancies compared the risk of stillbirth between fertile women, sub fertile women and women pregnant after fertility treatment (IVF and non-IVF ART).…”
Section: Discussionsupporting
confidence: 93%
“…Our low birth weight rate of 48.1% compares well with the range across various studies. Our study reports 22.6% neonates to be small for gestational age which also compares well with the 16.2% reported in a study of singleton neonates born following IVF [15]. Another study has reported double incidence of small for gestational age in IVF neonates than in non-IVF neonates [8].…”
Section: Discussionsupporting
confidence: 89%
“…(24)(25)(26)(27)(28)(29) These findings suggest that the elevated risk of gestational hypertension and preeclampsia in pregnancies resulting from infertility treatments is related to their higher proportion of twins and higher order gestations. However, controlling for multiple gestations would be unwarranted if the goal were to estimate the total impact of infertility treatments on the risk of gestational hypertension, whether or not this effect is mediated through multiple gestations.…”
Section: Discussionmentioning
confidence: 94%
“…(14,15) Among the more recent studies that adjusted for maternal age and parity and considered multiple gestations, some have found an increased risk in women receiving infertility treatments, even after stratification for number of fetuses, (16,17) or restriction to singletons (8,(18)(19)(20)(21) or multiple gestations. (22,23) Others have found no significant differences between assisted and spontaneous pregnancies after stratification, (24) or restriction to singletons (25)(26)(27)(28)(29) or multiple gestations. (29)(30)(31)(32)(33)(34) It thus remains unclear whether the association between infertility treatments and gestational hypertension is due to biologic factors intrinsic to couples with infertility problems, to patient characteristics such as older age and primiparity, to the higher rate of multiple gestations, or to the specific infertility treatment.…”
Section: Introductionmentioning
confidence: 98%